Curcumin-based ionic Pt(ii) complexes: antioxidant and antimicrobial activity. Issue 43 (18th October 2022) - Caligiuri, Rossella; Di Maio, Giuseppe; Godbert, Nicolas; Scarpelli, Francesca; Candreva, Angela; Rimoldi, Isabella; Facchetti, Giorgio; Lupo, Maria Giovanna; Sicilia, Emilia; Mazzone, Gloria; Ponte, Fortuna; Romeo, Isabella; et al.
Abstract : Four new Pt(ii ) ionic complexes assembled from N-donor ligands and curcumin display interesting antioxidant and antimicrobial properties. Abstract : A series of novel cationic curcumin-based Pt(ii ) complexes with neutral (N^N) ligands and triflate anions as counterions, [(N^N)Pt(curc)]CF3 SO3, 1–4, were synthesised and fully characterised. The antioxidant radical scavenging activity of complexes 1–4 was measured spectrophotometrically using DPPH as the internal probe. Computational strategies have been exploited to ascertain the mechanism of antioxidant action of curcumin (H(curc)) and its Pt(ii ) complexes. Finally, compounds 1–4 were tested in vitro for their growth inhibitory activity against two bacteria ( Staphylococcus aureus and Escherichia coli ) by the disk diffusion technique at different Pt(ii ) complex solution concentrations. The effect of the complexation of H(curc) was investigated.